Community-Based Rehabilitation of Critical Land at Jenar, Sragen, Central Java - S Suharjo (Universitas Muhammadiyah Surakarta, 2003)
The aims of the study of critical land rehabitation basing on the society in Jenar Sragen are to know: 1) the factory which cause the critical land; 2) the way to solve critical land; and 3) the role society in solving critical land. The collected date are 1) topography, 2) litologhy, 3) geomorphology, 4) soil, 5) hydrology, 6) land use, 7) the apportion of critical land, and 8) the way to solve critical land. The choice of sample uses purposive method, while the data analysis to get result uses descriptive method. The result of the study show that: 1) the distribution of critical land is in land unit of anticline hills of tuff rocks, marl, clay, and sand tuff which are denudated process by rensina soil and litosol from light to heavy which lie in dry land cultivation and forest. The factors which influence critical land are high rainfall (2178 mm), inclination slope (8 – 20%), solun soil whih is less than 20 cm and denudation process high is active; 2) the way that has been done is solving critical land rehabilitation is cooperation among the society, the forestry and commercial agricultural department and cone sugar factory of Mojo Sragen. The critical land which has been rehabilitated is state forest (266.95 ha) and the dry lang cultivation of the society (772.50 ha); 3) the society has responsibility for the growth, the development and preservation of the long term plants (jati, sonokeling, mahoni). The participation of the society in that programme is about 3.117 people.